Calling Older Workers Back to Work - Francesco Grigoli; Zsoka Koczan; Petia Topalova (Global Labor Organization (GLO), 2021)
Population aging in advanced economies could have significant macroeconomic implica- tions, unless more individuals choose to participate in labor markets. In this context, the steep increase in the share of older workers who remain economically active since the mid- 1990s is an overlooked yet encouraging trend. We identify the drivers of the rise in participa- tion of the elderly relying on cross-country and individual-level data from advanced economies over the past three decades. Our findings suggest that the bulk of the increase in their par- ticipation is driven by gains in educational attainment and changes in labor market policies, such as the tax benefit system, and pension reforms. Urbanization and the increasing role of services also contributed, while automation weighed on their participation.
Keywords: J11; J21; O33; 330; Automation; elderly; labor force participation; pension